Mercury Pictures presents : a novel [large type] - Marra, Anthony (Random House Large Print, 2022)
After America's entry into WWII, Maria Lagana, an associate producer at Mercury Pictures, rises through a maze of conflicting politics, divided loyalties, and jockeying positions until a man from her imprisoned father's past threatens her carefully constructed facade.